2019
DOI: 10.36040/ijsgset.v1i1.183
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Latitude Differences, Sunshine Periods, Solar Radiation Quantities and Air Temperatures on Solar Electricity Generation.

Abstract: Electricity supply has gained importance with the increase of electricity demand in the world. The energy that the sun can accept forever provides great convenience for electricity generation. In regions where the sun's rays are steep, it is easier to generate electricity from the solar energy, whereas in regions where the sun's rays are horizontal, the electricity production from the solar energy remains at a lower level. In this study, Istanbul and Adana are compared in the northern and southern regions of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…When the average annual temperatures are examined, Adana province is 19 °C and Istanbul province is 13.8 °C. Although the province of Istanbul has a lower average temperature, it has been found that it has a higher yield than the province of Adana [2]. The radiation energy of the sun's light itself will be absorbed and also reflected back before reaching the earth.…”
Section: Solar Light Radiation Energymentioning
confidence: 99%
“…When the average annual temperatures are examined, Adana province is 19 °C and Istanbul province is 13.8 °C. Although the province of Istanbul has a lower average temperature, it has been found that it has a higher yield than the province of Adana [2]. The radiation energy of the sun's light itself will be absorbed and also reflected back before reaching the earth.…”
Section: Solar Light Radiation Energymentioning
confidence: 99%
“…This concentration mechanism can be obtained by the reflection or refraction of solar radiation using mirrors or lens [8]. Reflected or refracted light is concentrated in the focus area.…”
Section: Introductionmentioning
confidence: 99%